"Kill Them All—Old and Young, Girls and Women and Little Children"1: An Examination of the Organizational Choice of Targeting Civilians. Issue 3 (9th February 2015) - Asal, Victor; Brown, Mitchell; Schulzke, Marcus
Abstract : What factors make it more likely that non-state organizations will target civilians as a political strategy? This study examines targeting civilians as a tactical and normative choice, and hypothesizes that the targeting of civilians (compared to the general use of violence) is a function of the ideological make-up of organizations, organization weakness and state repression. Other factors related to organizational capability will not have a differential impact on the likelihood that an organization will target civilians for violence. This article uses data from the Minorities at Risk Organizational Behavior database to examine these issues with respect to ethno-political organizations. It argues that the typical analytic focus on general violence obscures understanding of the factors that lead to targeting civilians. It finds that targeting civilians—while similar in some respects to the use of general violence—is different, particularly with respect to organizational ideology.